2000
DOI: 10.2136/sssaj2000.6441290x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preferential Flow on the Transport of Adsorbing and Non‐Adsorbing Tracers

Abstract: Field experiments were conducted by using a tile drain monitoring facility to determine the impact of preferential flow on the transport of adsorbing and non‐adsorbing tracers. Simulated rainfall with 7.5 mm h−1 intensity and 7.5 h duration was applied to a 18‐ by 65‐m no‐till plot. After 72 min of irrigation, a pulse of Br− and rhodamine WT (water tracer) was applied through irrigation, and 4 h later, a second pulse of Cl− and rhodamine WT was applied. The breakthrough curves (BTC) of these tracers were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 11 publications
10
97
2
4
Order By: Relevance
“…These results are similar to those observed by Kung et al (2000), who applied Br with the water in a 7.5 h irrigation event at a rate of 7.5 mm h 21 . Kung et al (2000) first observed Br in the tile drainage within 2 h of when a Br pulse was injected into the irrigation stream, reaching a peak concentration near 300 mg L 21 and then decreasing lognormally after that initial concentration spike. Increasing Br concentration through 13 to 17 h (Figure 2a) in this study was probably a consequence of the greater amount, and longer duration, of Br application.…”
Section: Bromide Concentrationsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to those observed by Kung et al (2000), who applied Br with the water in a 7.5 h irrigation event at a rate of 7.5 mm h 21 . Kung et al (2000) first observed Br in the tile drainage within 2 h of when a Br pulse was injected into the irrigation stream, reaching a peak concentration near 300 mg L 21 and then decreasing lognormally after that initial concentration spike. Increasing Br concentration through 13 to 17 h (Figure 2a) in this study was probably a consequence of the greater amount, and longer duration, of Br application.…”
Section: Bromide Concentrationsupporting
confidence: 90%
“…Although the Rhodamine WT peak concentration in the tile water occurred at the same time as the peak for the conservative tracers [nitrate (NO 3 ) and Br] in this study (Everts et al 1989), the Rhodamine WT concentration decreased to near background levels almost immediately with the cessation of irrigation, while the conservative tracer concentrations remained at a relatively elevated level. Kung et al (2000) demonstrated similar results using the same tracers on larger tiledrained plots (18 by 65 m) and included an evaluation of two irrigation intensities in no-tilled (NT) and conventionally tilled (CT) fields. Arrival time (to the tile outlet) was similar for both types of tracers, and they did not observe a difference between tillage practices.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…A parameterisation of the Freundlich isotherm based on values reported in the Footprint data base (www.eufootprint.org) did not reveal any meaningful result. Based on the finding of Zehe and Flühler (2001) at this site, who report an effective retardation coefficient of one at the end to the experiment and similar findings of Kung et al (2000) who found similar behaviour for bromide and the sorbing tracer rhodamin WT, we reduced the k f values and thus the retardation coefficient stepwise to one. With this, the proposed model approach could be attuned to reproduce the overall IPU mass that leached to the tile drain.…”
Section: Clear Deficiencies To Reproduce Observed Pesticides Leachingmentioning
confidence: 75%
“…Field investigations and modeling of water and tracer movement are important in studying numerous hydrological problems, including water resource contamination (Gödeke et al, 2006;Sudicky and Illman, 2011;Zheng et al, 2011), flood mitigation (Baker, 1987;Gubareva and Gartsman, 2010;Wood et al, 1990), and landslide initiation due to excess pore pressure generation (Iverson, 2000;Wilson et al, 2012). Usually the influence of PFP on mass transfer is determined experimentally by measuring water or tracer outflow from soil columns, lysimeters or in natural catchments (Everts and Kanwar, 1989;Ghodrati and Jury, 1992;Kung et al, 2000;Mallants et al, 1996;Tsuboyama et al, 1994;Vanderborght et al, 2000). Experimental data collected this way simplifies often tortuous flow pathways to a quasi-1-D process.…”
Section: Introductionmentioning
confidence: 99%